Research on the Development and Reform of IT Operation Monitoring and Management Platform for the Cloud Data Center - Haoshuang Song (Dianxin kexue)
Describes and analyzes the problems and needs of IT operation monitoring and management under the new environment of cloud data center, researches the development and reform of IT operation monitoring and management technology, summarizes and puts forward the ideas solution: cloudization, three-dimensional, intelligence, integration and shared services.